Digital Image Processing Using Coefficients of Sakaguchi Kind Function Defined in Limacon Shaped Domain with Power Law Transformation (Contemporary Mathematics, 2024)
Digital image processing is a constantly evolving field that focuses on digital image analysis, enhancement, and modification. Another popular approach used to improve the aesthetic appeal and diagnostic usefulness of images is power law transformation. Power law transformation and the analysis of analytic coefficients obtained from complex functions within digital image processing have become more popular recently. We demonstrate that analytic coefficients provide a solid foundation for investigating phase information in images and enhancing certain aspects of images. Complex image processing tasks, like spatial filtering, picture segmentation, and contrast enhancement, can be efficiently completed by combining power law transformation with analytical coefficients. This study focuses on applying analytic coefficients that come from a specific group of Sakaguchi-type functions are used to improve images by transmitting to a domain shaped like a Limacon. The article also provides a wide range of instances that highlight the usefulness of this method in the field of medical imaging. The results unequivocally highlight the significance of analytic coefficients and power law transformation as valuable tools for digital image processing.
Keywords: analytic function, subordination, image enhancement, image quality, quality metrics